Trauma-informed leadership in libraries - Crum, Janet; Ketchum, David (Emerald Publishing Limited, 2025)
Trauma-informed practices have become an increasingly essential part of librarianship since the COVID-19 global pandemic. Trauma can result from a single negative event or repeated exposure to negative events over time and can manifest in many forms. Trauma-informed approaches to leadership seek to understand and consider an individual's holistic life experiences, particularly negative consequences of trauma, when determining how to best support and interact with them in the workplace.
Includes index.
Keywords: Academic libraries -- Administration.; Language Arts & Disciplines -- Library & Information Science -- Administration & Management.; Library, archive and information management.; elektronické knihy; electronic books